Evaluating the implementation of national recommendations on multidrug-resistant bacterial microorganisms in end-of-life care - Heckel, Maria; Illig, Annabell; Brunner, Sarah; Ostgathe, Christoph (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2020)
Introduction: In 2017, a national recommendation on multidrug-resistant bacterial microorganisms (MDRO) in end-of-life care was published. In order to monitor the implementation in a hospital-based palliative care unit, a dedicated multidisciplinary working group on MDRO was established. It developed a standard operating procedure and a documentation template (checklist). The aim of the present study is to evaluate the implementation status after one year. Methods: A mixed-methods approach was selected. The status of implementation was identified through a survey among staff members. A retrospective routine data analysis was performed. A focus group discussion with members of the working group focused on previous steps, factors conducive to implementation and on remaining problems. Results: Almost all (18 out of 20) participants (20 out of 29 eligible staff members) knew the national recommendations. Twelve out of 27 recommendations had a high degree of implementation after one year, another 13 recommendations were seen as at least partly integrated into daily routine. For two recommendations the degree of implementation was rated low: (i) ”Taking into account any additional time constraint imposed by protection and isolation measures when planning for personnel and bed occupancy”, and (ii) ”Facilitating the patient's ability to distinguish and recognize team members and family caregivers”. Working group members reported improvements since the implementation, whilst reporting some uncertainty prevailing among both staff members and visitors. Inhibitory factors were said to include the complexity of the standard operating procedure, inadequate usage and poor usability of the checklist. Behavioural and cognitive barriers such as anxieties related to transmission and the sense of security caused by the routine use of protective clothing were considered to be strong. Improving the checklist and the standard operating procedure as well as anchoring procedures in daily routine were considered to be the next important steps. Discussion: The implementation of recommendations is an iterative process and requires the ongoing development of appropriate measures for implementation in the respective institution. A multidisciplinary working group with monitoring tasks is an advantage.
CRIS-Team Scopus Importer:2020-11-20
Keywords: End-of-life care; Evaluation research; Infection control; Palliative care; Patient safety